Clinician's guide to neuropsychological assessment. - Vanderploeg, Rodney D., ....- (Mahwah : Lawrence Erlbaum, 2000)
Neuropsychological assessment is a difficult and complicated process. Often, experienced clinicians as well as trainees and students gloss over fundamental problems or fail to consider potential sources of error. Since formal test data on the surface appear unambiguous and objective, they may fall into the habit of overemphasizing tests and their scores and underemphasizing all the factors that affect the validity, reliability, and interpretability of test data. But interpretation is far from straightforward, and a pragmatic application of assessment results requires attention to a multitude of issues. This long-awaited, updated, and greatly expanded second edition of the Clinician's Guide to Neuropsychological Assessment, like the first, focuses on the clinical practice of neuropsychology. Orienting readers to the entire multitude of issues, it guides them step by step through evaluation and helps them avoid common misconceptions, mistakes, and methodological pitfalls. It is divided into three sections: fundamental elements of the assessment process; special issues, settings, and populations; and new approaches and methodologies. The authors, all of whom are actively engaged in the clinical practice of neuropsychological assessment, as well as in teaching and research, do an outstanding job of integrating the academic and the practical. The Clinician's Guide to Neuropsychological Assessment, Second Edition will be welcomed as a text for graduate courses but also as an invaluable hands-on handbook for interns, postdoctoral fellows, and experienced neuropsychologists alike. No other book offers its combination of breadth across batteries and approaches, depth, and practicality.
Keywords: Neuropsychologie -- Diagnostiek